Medicinal and Nutritional Significance of Grey Mangroves Marine Plant: An Underutilized Resource - Arshad Rasool; Wasiq Ikram; Tian Tian; Ishrat Fatima; Ab Waheed Wani (Journal of Nautical Eye and Strategic Studies, 2023)
Grey Mangroves are widely distributed worldwide and provide a wide range of medicinal and nutritional benefits. These plants have been traditionally used to treat a variety of ailments including cancer and diabetes. This article reviews the current research on the significance of grey mangroves in all over the world especially Pakistan and suggests ways in which these resources can be better utilized to improve health outcomes. While the medicinal and nutritional properties of grey mangroves have been recognized for centuries, their potential has yet to be fully realized. Further research is needed to identify, isolate the active compounds to develop novel drugs and nutritional supplements. Finally, efforts should be made to increase public awareness of the health benefits of grey mangroves, so that more people can benefit from their medicinal and nutritional properties.